Blast furnace ironmaking : analysis, control, and optimization - Cameron, Ian; Sukhram, Mitren; Lefebvre, Kyle; Davenport, William (Amsterdam, Netherlands : Elsevier, 2020)
'Blast Furnace Ironmaking' uses a fundamental first principles approach to prepare a blast furnace mass and energy balance in ExcelT. Robust descriptions of the main equipment and systems, process technologies, and best practices used in a modern blast furnace plant are detailed. Optimisation tools are provided to help the reader find the best blast furnace fuel mix and related costs, maximise output, or evaluate other operational strategies using the ExcelT model that the reader will develop. The first principles blast furnace ExcelT model allows for more comprehensive process assessments than the 'rules of thumb' currently used by the industry. This book is suitable for undergraduate and postgraduate science and engineering students in the fields of chemical, mechanical, metallurgical and materials engineering.
Includes bibliographical references and index.
Keywords: Blast furnaces; Smelting